Whitney A. Bauman (ed.), Meaningful Flesh: Reflections on Religion and Nature for a Queer Planet. (3rd May 2019) - Keller, Mary
Abstract : Whitney A. Bauman (ed.), Meaningful Flesh: Reflections on Religion and Nature for a Queer Planet (Goleta, CA: Punctum Books, 2018), 149 pp., 19.00 (pbk), ISBN: 9781947447325.